2018
DOI: 10.1159/000479825
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Influence of pH on Metalloproteinase Activity in Human Coronal and Radicular Dentin

Abstract: The aim of this study was to evaluate the effect of pH on the activation of matrix metalloproteinases (MMPs) of human coronal (CD) and radicular dentin (RD). CD and RD were pulverized to powder, and proteins were extracted with 1% phosphoric acid. The extracted proteins and the demineralized powder were separately incubated in the following solutions: 4-aminophenylmercuric acetate (control) or a buffer solution at different pHs (2.5, 4.5, 5.0, 6.0, and 7.0). After incubation, proteins were separated by electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In order to sustain an infection associated with chronic inflammation, the bacteria must be able to resist or protect themselves from common canal irrigants, taking refuge in the lateral canals or dentinal tubules—spaces with a greater level of protection from antimicrobial agents. In addition, dentine acts as a natural buffer to increase the pH induced by the use of calcium hydroxide-based medications [46].…”
Section: Discussionmentioning
confidence: 99%
“…In order to sustain an infection associated with chronic inflammation, the bacteria must be able to resist or protect themselves from common canal irrigants, taking refuge in the lateral canals or dentinal tubules—spaces with a greater level of protection from antimicrobial agents. In addition, dentine acts as a natural buffer to increase the pH induced by the use of calcium hydroxide-based medications [46].…”
Section: Discussionmentioning
confidence: 99%
“…Metalloprotease activity can be dependent on pH 40 42 , begging the question whether MT1-MMP cleavage can be affected by the acidic endosomal pH. Indeed, deacidification of endosomes using NH 4 Cl reduced MT1-MMP shedding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon can be explained by the acidic nature of the novel dressing material, as MMPs show maximum activity at an alkaline pH of ~ 8. The MMP-2 enzyme is dynamically influenced by the pH: at a low pH, the extracted enzyme activates a latent form, whereas collagen degradation by the matrix-bound enzyme is only observed at a pH close to neutral (Amaral et al 2018). In a study by Khajah et al (2013), the authors demonstrated an increased MMP-2/9 activity in response to the elevated extracellular pH.…”
Section: Discussionmentioning
confidence: 99%